PENERAPAN STRATEGI PEMBELAJARAN KREATIF PRODUKTIF DIKOLABORASIKAN DENGAN MNEMONIK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA KONSEP PENCEMARAN LINGKUNGAN DI KELAS X MA PUI TENAJAR INDRAMAYU - Ulinniam (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2020)
The learning process is to develop students' activities and creativity through various interactions and various learning experiences. But in its implementation, learning is still found that does not develop the potential of the students to be active and creative in learning. The purpose of this study (1) to study the activities of students who apply productive creative learning strategies collaborated with mnemonics, (2) find out the difference in learning outcomes improvement of students who apply productive creative learning strategies collaborated with mnemonics with those who do not use, (3) examine participant responses students with the implementation of productive creative learning strategies collaborated with mnemonics. The approach used in this research is a quantitative approach. The population in this study were all students of class X MA PUI Tenajar Indramayu with a sample of 2 experimental and control classes. The results of this study indicate that: (1) the activities of the students went quite well, this is based on the value of the observation sheet the average student was able to get a value of 77.8. (2) there is a difference in the improvement of student learning outcomes between the experimental and control classes, this is seen from the results of the Paired Sample Test which shows the significance value or sig (2- tailed) is 0,000, when compared the value will be less than 0.05 (0,000 <0.05), (3) students' responses to the application of productive creative learning strategies collaborated with mnemonics on the concept of environmental pollution categorized as strong, this is seen from the average percentage of positive statements 76.3% and negative statements 69, 2% who answered agreed, in other words the majority of students liked productive creative learning strategies collaborated with mnemonics.